The concept of time in the theological thought of Sayyid Abdul Rahim Al-Mawlawi - أحمد, د. سعدون حسين (Sulaimani Journal for Humanities, 2025)
The topic of time and its essence was discussed from different dimensions and with different approaches. Time was the subject of research for philosophers, and they presented rational theories and analyzes about the essence of time and its parts. All of these opinions were theorized with different philosophical approaches. These researches left methodological imprints outside the circle of philosophy, as Islamic theological schools were influenced. From time to time in these curricula in varying proportions, the topic of time is one of the topics that was discussed at the beginning of the science of speech. Each school began researching the topic of time, and they came up with different opinions on the topic. Based on this rich heritage, Sayyid Abdul Rahim Al-Mawlawi began researching the subject and its philosophical and theological dimensions. His opinions revolved around the circle of the Ash’ari school of thought when he searched for time and its essence. He was not satisfied with what the philosophical schools said regarding the essence of time. He expressed new indications regarding the subject of time and its details.
Keywords: concept; time; thought; speech; Mawlawi